1978
DOI: 10.1136/gut.19.8.729
|View full text |Cite
|
Sign up to set email alerts
|

Factors which influenced postoperative complications in patients with ulcerative colitis or Crohn's disease of the colon on corticosteroids

Abstract: The study revealed no correlation between steroid dosage and postoperative morbidity or mortality. The incidence of wound dehiscence and incisional hernia compared favourably with the reports of other unselected series of similar patients. Contamination did significantly influence results. Septic complications were more frequent when the operative field was contaminated and both delayed wound healing and mortality were related to this sepsis. A 'clean and dirty' technique was effective in controlling contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
2

Year Published

1979
1979
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 9 publications
1
12
1
2
Order By: Relevance
“…Yamamoto (17) and Post (18) both found that preoperative corticosteroid therapy was associated with a high incidence of postoperative septic complications in multivariate analyses. However, other investigators were not able to demonstrate an increased risk of postoperative septic complications in patients under treatment with corticosteroids at the time of operation for CD (23,28,29). Experimental data indicate that use of very high doses of corticosteroids may be associated with impaired anastomotic healing (30).…”
Section: Discussionmentioning
confidence: 99%
“…Yamamoto (17) and Post (18) both found that preoperative corticosteroid therapy was associated with a high incidence of postoperative septic complications in multivariate analyses. However, other investigators were not able to demonstrate an increased risk of postoperative septic complications in patients under treatment with corticosteroids at the time of operation for CD (23,28,29). Experimental data indicate that use of very high doses of corticosteroids may be associated with impaired anastomotic healing (30).…”
Section: Discussionmentioning
confidence: 99%
“…The septic complication rate after strictureplasty was similar or lower to that (3-50 percent) after bowel resection for Crohn_s disease. [82][83][84][85][86][87][88][89][90][91] Other complications included hemorrhage, ileus, wound infection, and bowel obstruction, but their incidence was low. Although major hemorrhage was rare, several patients, especially after multiple strictureplasties, required angiography to identify the bleeding site and intra-arterial vasopressin infusion.…”
Section: Jejunoileal Strictureplastymentioning
confidence: 97%
“…The complication rate after ileocolonic strictureplasty was similar to that after bowel resection. [87][88][89][90][91][92][93][94][95][96] The long-term Vol. 50,No.…”
Section: Ileocolonic Strictureplastymentioning
confidence: 99%
“…Wound disruption occurred in only 1.3% of our series, which is comparable with the experience of others. [17][18][19][20][21][22] The large number of patients requiring ileostomy has resulted in considerable morbidity. The use of the Brooke eversión ileostomy23 has almost eliminated the complica¬ tion of nonspecific serositis, only three cases of early ileostomy dysfunction being recorded, and all six cases of late dysfunction being caused by recurrent disease.…”
Section: Early Postoperative Complicationsmentioning
confidence: 99%